2008
DOI: 10.1158/1078-0432.ccr-07-4960
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Differences Between Pure Ductal Carcinoma In Situ of the Breast and that Associated with Invasive Disease: a Calibrated aCGH Study

Abstract: Purpose: In the quest for new targets, genomes of ductal carcinoma in situ (DCIS) and infiltrating duct carcinoma (IDC) have been compared previously; however, genomic alterations associated with cancer progression were difficult to identify. We hypothesized that significant events can be detected by comparing lesions with a broader range of behavior: from pure DCIS to IDC associated with lymph node metastasis. Experimental Design: Array comparative genomic hybridization, calibrated by self-self hybridization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 37 publications
(55 reference statements)
7
49
0
Order By: Relevance
“…It remains challenging to build a comprehensive picture of the events involved in progression of pure DCIS to invasive cancer with any certainty. Complex, branched models are proposed, with multiple mutational events driving multiple routes to invasive cancer [17][18][19], however recent data suggests that at least some fraction of pure DCIS may be molecularly distinct from DCIS which is identified associated with invasive cancer [20,21]. It may be that some DCIS may not develop the molecular alterations which lead to invasive cancer and therefore may represent a molecular state with low risk of progression.…”
Section: Imaging Tissue Banks and Translational Researchmentioning
confidence: 99%
“…It remains challenging to build a comprehensive picture of the events involved in progression of pure DCIS to invasive cancer with any certainty. Complex, branched models are proposed, with multiple mutational events driving multiple routes to invasive cancer [17][18][19], however recent data suggests that at least some fraction of pure DCIS may be molecularly distinct from DCIS which is identified associated with invasive cancer [20,21]. It may be that some DCIS may not develop the molecular alterations which lead to invasive cancer and therefore may represent a molecular state with low risk of progression.…”
Section: Imaging Tissue Banks and Translational Researchmentioning
confidence: 99%
“…DCIS has long been known to be heterogeneous in its morphologic features, presentation, and clinical behavior. The emergence of genomic and gene expression profiling has established that DCIS is heterogeneous at a level of molecular complexity that is comparable with or perhaps greater than that of invasive disease (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Although certainly less studied, the heterogeneity observed in the microenvironment surrounding individual premalignant lesions may also be a critical determinant of their future behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In tumours containing both IDC and DCIS (IDC-DCIS), it is unclear whether the IDC component arises directly from DCIS; in tumours lacking DCIS, however, it is assumed that IDC arises de novo. One recent study implicated DCIS as the precursor of IDC-DCIS based on concordant expression of immunohistochemical markers (Steinman et al, 2007), a conclusion that has since been supported by genomic data (Aubele et al, 2000;Alexe et al, 2007;Iakovlev et al, 2008), in turn creating a quest for biomarkers that predict invasive transformation of DCIS (Schuetz et al, 2006;Castro et al, 2008). Other studies have reported differences between DCIS and IDC-DCIS, suggesting that DCIS may not have been a precursor of the invasive component (Farabegoli et al, 2002); however, some of these studies have been limited either by failure to use pure IDC as a comparator (Patla et al, 2002) or else by small cohort sizes (Mylonas et al, 2005).…”
mentioning
confidence: 96%